Routledge international handbook of the sociology of art and culture - Hanquinet, Laurie; Savage, Michael (Routledge international handbooks, 2015)
pt. 1. Bourdieu's legacy and new perspectives for the sociology of art and culture -- pt. 2. The fabric of aesthetics -- pt. 3. The complexity of cultural classifications